Isolation and structure elucidation of gibberillin produced by Plant Growth Promoting Bacteria (PGPB) and its effect on the growth of hybrid rice (Oryza sativa L.) (The Philippine Journal of Crop Science, 2010)
Forty plant growth promoting bacteria (PGPB) were screened for gibberellin (GA) production through the dwarf rice (cv. Tanginbozu) bioassay. Among the GA-producing isolates, TCeR 48 produced the highest amount of GA (81.70 ug GA3 equiv mL1 culture). The peak of GA production by TCeR 48 was at 15 days after inoculation. Extracts from TCeR were purified by high performance liquid chromatography (HPLC) and analyzed through gas chromatography coupled with mass spectrometry (GC-MS). The production of ent-kaur-16-ene, an intermediate in the biosynthesis of gibberellin, is indicated by the peaks at m/z 91 and m/z 105. There is a hint that GA20 is present due to peaks at m/z 375 and 418 which are similar to the structure of GA20, a 13-hydroxy gibberellin. Further analysis by ultraviolet (UV) spectroscopy revealed the presence of a strong peak at Amax of 215 nm which indicates the presence of uncojugated –OH bond and a low intensity single bond at Amax of 260 nm which suggests the presence of isolated C=O and –COOH. Fourier transform infrared (FTIR) spectroscopy confirmed the functional groups present in the unknown GA structure. Peaks at 3377.95 cm-1 and 1411.99 CM-1 suggest the presence of of –COOH and –CH3 groups, respectively. All of the observed functional groups in the UV and FTIR spectra are characteristics of the structure of GA20. However, a distinct peak at 116.98 cm-1 of the TCeR 48 spectrum indicates the presence of a double bond in the structure of the unknown GA which is absent in GA20.